The functional variability of goal-directed movements in football - Carrilho, D.; Albaladejo-García, C.; Lopes, H.; Vaz de Carvalho, M.; Moreno, F. J.; Araújo, D. (International Journal of Sports Physiology and Performance, 2025)
Background: Research highlights that understanding movement functionality in football requires contextualizing physical demands. Ecological dynamics provides a useful framework for this contextualization by examining how players adjust their action capabilities (effectivities) to opportunities for action in the match environment (affordances).